Study of the heavy metals in fume of buckshot, blood lead concentration and self-rated health status of national clay shooting athletes - Chun, H.-J.; Nam, S.-M.; Cho, I.-H. (The Korean Journal of Sports Medicine, 2018)
Purpose: This study was conducted to investigate the levels of heavy metals and self-rated health status of the national clay shooting athletes. Methods: Fourteen subjects` blood lead level and index of liver damage (aspartate aminotransferase, alanine aminotransferase, and Gamma-glutamyl transferase) were measured. Heavy metal content in training environment was measured by collecting the buckshot fume. In addition, subjects completed a questionnaire assessing self-rated health status (Todai Health Index). Results: Antimony and lead were detected much more than other heavy metals in the air of the shooting range. The average blood lead level of 14 subjects was significantly higher than the upper limit of normal Korean adults. Blood lead level of male is significantly higher than female and training frequency and the total training time per week were positively correlated to the blood lead level. In the result of survey on self-rated health, the higher the blood lead level, the lower the score of the common subjective physical symptoms. By age, the younger the subjects are, the higher the score of the common subjective symptoms. Conclusion: Although the level of heavy metals in fume of buckshot and blood lead was high, national clay shooting athletes thought that they are healthy.